2020
DOI: 10.18632/aging.103632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of chronic liver disease with coronavirus disease 2019 (COVID-19): a cohort study in Wuhan, China

Abstract: Background: Previous work has described acute liver injury (ALI) in coronavirus disease 2019 (COVID-19) pneumonia patients, However, there is limited analyses available investigating chronic liver disease (CLD) in COVID-19 patients. This study aimed to investigate clinical characteristics and outcomes of CLD confirmed in COVID-19 patients. Results: A total of 104 cases (each group containing 52 patients) were analyzed in this study. The CLD group showed an average of 14 (10.0~21.2) length of stay (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The previous study elucidated the high mortality rate among CLD patient who they are Covid-19 infected. 23 , 24 Our findings also highlighted the high mortality rate and the long period of hospitalisation among cancer patients. The nature of cancer and the antineoplastic agents compromise the immune system.…”
Section: Discussionsupporting
confidence: 58%
“…The previous study elucidated the high mortality rate among CLD patient who they are Covid-19 infected. 23 , 24 Our findings also highlighted the high mortality rate and the long period of hospitalisation among cancer patients. The nature of cancer and the antineoplastic agents compromise the immune system.…”
Section: Discussionsupporting
confidence: 58%
“…The risk of death in COVID‐19 patients with chronic liver disorders was compared with that in ones without the CLD in 15 studies 19,26,28–40,42 . In all of these studies, the mortality rate in patients with COVID‐19, and the CLD was higher than that in patients with COVID‐19, and without the CLD 19,26,28,30,32–34,36–40 . The cumulative RR after combining these studies was 1.52 (CI 95%: 1.46–1.57; I 2 : 86.14%) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 26 studies reported on the mortality outcome among CLD and non-CLD patients (8,(10)(11)(12)15,19,20,22,(24)(25)(26)29,30,33,35,38,39,41,(44)(45)(46)(47)(48)(49)(50)(51). The pooled OR was 2.35 (95% CI, 1.84-3.00; I 2 = 96.26%; 95% PI, 0.76-7.18) (Figure 3), indicating that COVID-19 patients with CLD had 2.35 times higher odds of dying as patients without CLD.…”
Section: Mortalitymentioning
confidence: 99%